2015
DOI: 10.1002/2014jc010646
|View full text |Cite
|
Sign up to set email alerts
|

Decadal and seasonal changes in temperature, salinity, nitrate, and chlorophyll in inshore and offshore waters along southeast Australia

Abstract: Sixty years of oceanographic in situ data at Port Hacking (348S) and Maria Island (428S) and 15 years of satellite-derived chlorophyll a (chl a) in inshore and offshore waters of southeast Australia show changes in the seasonality and trend of water properties consistent with long-term intensification and southerly extensions of East Australian Current (EAC) water. Decadal analyses reveal that the EAC extension water at Maria Island increased gradually from the 1940s to 1980s, followed by a rapid increase sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
2
3
1
Order By: Relevance
“…In contrast, our results show that NPP peaks during winter at Port Hacking, when cooling waters create deeper mixed layer depths (Everett and Doblin, 2015) and have higher dissolved nitrate concentrations (Kelly et al, 2015). Chlorophyll-a concentration, although not always synchronous with NPP, is also negatively correlated to in-situ water temperature, and winter and spring concentrations have been shown to be comparable (Everett and Doblin, 2015;Kelly et al, 2015).…”
Section: Phytoplankton Absorption Model Predicts Nppcontrasting
confidence: 74%
See 1 more Smart Citation
“…In contrast, our results show that NPP peaks during winter at Port Hacking, when cooling waters create deeper mixed layer depths (Everett and Doblin, 2015) and have higher dissolved nitrate concentrations (Kelly et al, 2015). Chlorophyll-a concentration, although not always synchronous with NPP, is also negatively correlated to in-situ water temperature, and winter and spring concentrations have been shown to be comparable (Everett and Doblin, 2015;Kelly et al, 2015).…”
Section: Phytoplankton Absorption Model Predicts Nppcontrasting
confidence: 74%
“…In-situ observations and satellite (a PHY derived) estimates of surface NPP were comparable to those reported (for 13 C and 14 C incubations) in the literature for the North-west Kimberley region and in the North (0.6-8 mmol C m -3 d -1 ; Furnas and Carpenter, 2016 and references therein), GBR (0.2-4.1 mmol C m -3 d -1 ; Furnas and Carpenter, 2016;Furnas and Mitchell, 1987) and South-east (0.1-5 mmol C m -3 d -1 ; Everett and Doblin, 2015; See also Figure 7). We observed the highest in-situ daily NPP rates at stations in the South-east (V2 and PHNRS) and expected that the mean in-situ daily NPP would also peak in this region (Everett and Doblin, 2015) given the propensity for wind-driven and EAC driven upwelling (Roughan and Middleton, 2002) which encourages the growth of nanoplankton and microplankton (Ajani et al, 2014;Kelly et al, 2015). Generally, the oligotrophic Coral Sea region of the North-east supports very low phytoplankton biomass (Hayes et al, 2005).…”
Section: Phytoplankton Absorption Model Predicts Nppmentioning
confidence: 82%
“…show that the shelf warming in the EAC southern extension is almost solely advection-driven (Malan et al, 2021), changes in remote forcing effects seem more likely to be the main drivers of the trends that we see at Port Hacking and Maria Island. The accelerating warming at Maria Island, particularly since the 1980s, is also consistent with Kelly et al (2015) who showed that the amount of EAC extension water at this site rapidly increased over the same time period.…”
Section: Short-term Trendssupporting
confidence: 87%
“…In order to provide a comprehensive record of temperature trends in our region, we compare our results with previous studies that have investigated some aspect of temperature trends at or close to the sites used in this study (Wijffels et al, 2018;Malan et al, 2021;Thompson et al, 2009;Ridgway, 2007;Hill et al, 2008;Shears and Bowen, 2017;Holbrook and Bindoff, 1997;Kelly et al, 2015;Foster et al, 2014). Each of these studies have used linear methods to estimate the trends, and most studies have used surface data only.…”
Section: Comparison With Trends From Other Studiesmentioning
confidence: 99%
“…Tasman Sea Blocking (TSB) events also significantly affect the atmospheric circulation and rainfall patterns in the region (Pook & Gibson, ), and may influence the nearshore marine climate but this has yet to be demonstrated. Nearer to the Tasmanian coast, observations of trends and variability have been restricted to the relatively long Maria Island record, which exhibits significant multidecadal increases in temperature, salinity, and nitrate (Kelly et al, ). On the other hand, very little is known about the trends or variability in the ZC or the spatial distribution of multidecadal trends in temperature and salinity over the shelf.…”
Section: Introductionmentioning
confidence: 99%